The leisure of Kharkiv dwellers in the 70-ies the XIX century - Удовенкоu, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
In the article the big cities’ residents’ new spectacular mass entertainment in Russian Empire is analyzed at Kharkiv’ example. The facts of ballooning introduction in Kharkiv, eyewitnesses’ testimonies of first aeronauts’ flights are presented. It was set that ballooning got a wide social resonance and considered to be a new kind of spectacular entertainments.